Positron emission tomography – computed tomography as a monitoring response tool in pre-fibrotic myelofibrosis: a case report - Amna Qamar Uz Zaman; Shabbir Hussain; Zaheer, Ramsha; Andleeb, Madiha; Raza, Saba; Siddiqui, Tariq (Journal of the Pakistan Medical Association, 2022)
Primary myelofibrosis is a haematopoietic stem cell neoplasm resulting in ineffective haematopoiesis and bone marrow fibrosis. We present a case of a 67-year-old male patient who came to the oncology/haematology department of Dr. Ziauddin Hospital, Karachi, in February 2020 with complaints of weight loss, gastroesophageal reflux and loss of appetite. Continue...